2023
DOI: 10.1177/25152459231168024
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Repeated-Measures Analysis of Variance: An Updated Methodology Implemented in JASP

Abstract: Analysis of variance (ANOVA) is widely used to assess the influence of one or more experimental (or quasi-experimental) manipulations on a continuous outcome. Traditionally, ANOVA is carried out in a frequentist manner using p values, but a Bayesian alternative has been proposed. Assuming that the proposed Bayesian ANOVA is closely modeled after its frequentist counterpart, one may be surprised to find that the two can yield very different conclusions when the design involves multiple repeated-measures factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We used SBC to demonstrate that analyses based on aggregate data can lead to biases in the resulting null hypothesis tests, and should therefore be avoided. We demonstrated that biases in inferences do not only occur in frequentist approaches, where these are well-known and routinely corrected using frequentist tools, but that they also apply in Bayesian data analysis using Bayes factors, where they are often neglected (van den Bergh et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used SBC to demonstrate that analyses based on aggregate data can lead to biases in the resulting null hypothesis tests, and should therefore be avoided. We demonstrated that biases in inferences do not only occur in frequentist approaches, where these are well-known and routinely corrected using frequentist tools, but that they also apply in Bayesian data analysis using Bayes factors, where they are often neglected (van den Bergh et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For such aggregated data, it is not possible to estimate all random effect variances for the different effects (contrasts). Instead, only some of the random effects are informed by the data (van den Bergh et al, 2023). For example, in a one-factor design, only random intercepts are informed, but not random slopes; in a two-factor design, only random slopes for the main effects are informed by the data, but not random slopes for the interaction.…”
Section: Issue 1: Bayes Factors For Aggregated Data Are Biased If Ran...mentioning
confidence: 99%
See 2 more Smart Citations
“…The scaling of priors was set to default, and BFs were calculated in analogy to the Type III tests in classical frequentist ANOVA. Note that there has been a recent debate about the shortcomings of Bayesian ANOVA (when implemented as a mixed model) with default settings (Singmann et al, 2023; van den Bergh et al, 2023). We thus report the corresponding BFs for consistency, but remain a main focus on the classical frequentist ANOVA.…”
Section: Methodsmentioning
confidence: 99%